Prenatal diagnosis of congenital fetal heart abnormalities and clinical analysis - Li, Hui (Zhejiang University Press, 2005)

(untitled)
Objective: To study the value of detecting fetal congenital heart disease (CHD) using the five transverse planes technique of fetal echocardiography. Methods: Nine hundred and eighty-two high-risk pregnancies for fetal CHD were included in this study, the fetal heart was scanned with the five transverse planes technique of fetal echocardiography described by Yagel, autopsy was conducted when pregnancy was terminated. Blood from fetal heart was collected for fetal chromosome analysis. A close follow-up was given for normal fetal heart pregnancies and neonatal echocardiography was performed to check the accuracy of prenatal diagnosis. Results: (1) Forty-six cases (4.68%) were found to have fetal heart abnormalities in this study, 69.56% of them were diagnosed by single four-chamber view, another 30.43% fetal CHD were found by combining other views; (2) Forty-one parents of prenatal fetuses with CHD chose to terminate pregnancy, thirty-two of them gave consent to conduct autopsy, 93.75% of which yielded unanimous conclusion between prenatal fetal echocardiography and autopsy; (3) Thirty-two of 46 cases underwent fetal chromosome analysis, 8 cases (25%) were found to have abnormal chromosome; (4) Five cases were found to have right ventricle and atrium a little bigger than those on the left side, with the unequal condition being the same after birth, but there were no clinical manifestations and they are healthy for the time being; (5) Nine hundred and thirty-six cases were not found with abnormality in this study, but one case was diagnosed with ventricular septal defect after birth, one case was diagnosed with patent ductus arteriosus, one case had atrial septal defect after birth. Conclusions: (1) The detected CHD rate was 4.68% by screening fetal heart with five transverse planes according to Yagel’s description of high risk population basis for CHD. The coinciding rate of prenatal diagnosis and autopsy was 93.75%; (2) The sensitivity of detecting fetal heart abnormality is 92%, the specificity is 99.6% using the five transverse planes technique of fetal echocardiography; (3) Fetuses with mild or moderate disproportion of right and left side in the heart are potentially healthy babies.